Control interno sobre la gestión crediticia y su incidencia en la rentabilidad de la Cooperativa de Ahorro y Crédito Futuro Lamanense del cantón La Maná periodo 2017 – 2018. - Vega Caiza, Magaly Mercedes (2019)
The present work was carried out with the purpose of analyzing the credit management through the application of internal control questionnaires in the Savings and Loans Cooperative “Futuro Lamanense” in La Maná, because the credit risks could significantly affect the profitability of the same. The methodology used for the development of the research was the deductive method that helped to analyze from general to particular the evolution of the provisions of the years 2017-2018, through the descriptive method was described by graphs the evolution of the defaulting between the real estate, micro and consumer credit portfolios, and the statistical method helped to establish the population size and statistical calculation for the elaboration of the graphs. In addition, bibliographic research was used to collect theoretical information on risks, provisions and field research due to the cooperative's facilities for the application of the interviews and the internal control questionnaire to the credit area. The analysis of the internal control of the credit area reflected the following findings: inadequate protection of the mortgage deeds, the business executive does not have a credit recovery control of the credit counselors, the client does not receive explanations or deliver copies of the credit liquidation, no new loan reports are prepared, no procedures to communicate timely about the expiration of the installments, no follow-up of the loans granted without guarantees, the analysis of the information obtained from the financial statements of each month of the years 2017-2018, reflected that the indicator of defaulting was reduced, placing itself at an acceptable percentage at the end of 2018. While the comparison between the defaulting of micro credit, consumption and real estate credit, evidenced the greater part of defaulting in the microcredit segment, in small swaths the consumer and real estate credit. As a proposal, a credit risk control manual was prepared for the savings cooperative and Loans “Futuro Lamanense”, which consisted of flowcharts of credit approvals, disbursements, policies to grant credits that will contribute significantly to the improvement of the quality of service and the level of profitability of this important financial institution in La Maná.